Sperm DNA Integrity and Some Immune Biomarkers are Related in Pyospermia as Compare with Control Group - Ali, Hasan Hadi (Journal of Science in Medicine and Life, 2025)
Inflammation of the semen and the resulting secretions is a problem in the male body. One of the most prominent problems caused by prostatitis is a bacterial infection. Infections cause a lot of pain during urination, as well as pain during intercourse and ejaculation. It has a very harmful effect on men and may sometimes lead to infertility. The aim is find out how the effects of some diseases are linked to certain biomarkers through this work. Materials and Methods: Semen specimen were collected from infertile patients with sperm infections, as well as a control group, who visited the fertility center at Al-Sadr Hospital in Najaf Governorate. The average age of infertile patients was (36.15 ± 2.16) years. The number of examined specimen was 90 specimen. The results showed that normal sperm morphology was a lot less in Pyospermia when compared to the control group. The result also show and significantly increased in Round cell concentration in Pyospermia when compared with control group. There is also significant increase in Interleukin 8 level, Malonaldehyde concentration and Antisperm antibody level in Pyospermia patients compared with control group. Conclusion: - Pyospermia, elevated inflammatory markers like IL-8, and the presence of antisperm antibodies significantly impact male fertility by inducing inflammation, oxidative stress, and immune-mediated sperm dysfunction. Early diagnosis and targeted interventions—ranging from antimicrobial and antioxidant therapy to assisted reproductive technologies—are crucial in managing these conditions and improving reproductive outcomes.